Internal structure of the Late Triassic Central Patagonian batholith at Gastre, southern Argentina: Implications for pluton emplacement and the Gastre fault system - Zaffarana, Claudia Beatriz (2017)
Fil: Zaffarana, Claudia Beatriz. Instituto de Investigación en Paleobiología y Geología, Consejo Nacional de Investigaciones Científicas y Técnicas. Argentina.